(untitled) (International Journal of Engineering and Computer Science, 2017)
The proposed system involves creating the 3D model of the SKNSCOE Korti, Pandharpur campus into a virtual model. The model is represented in two ways: A pre-rendered video sequence. The information begins by introducing the project area of virtual urban modeling in general terms. It discusses the modeling process of each building, the problems encountered and what has been done to solve these problems. Lastly, the information discusses the possibilities of future work that can be applied to this project. Appendix A contains the video and real-time application this project has produced. The initial results of reconstructing SKNSCOE Korti, Pandharpur 3D virtual model and future research directions are presented. Unity3D, which is usually treated as game development software, as a virtual reality development platform. The hierarchical approach of geographic information system is adopted in the study area.